Clinical characteristics and radiation therapy modality of younger patients with early-stage endometrial cancer, a multicenter study in China’s real world - Kun Zhang; Tiejun Wang; Zi Liu; Jianli He; Xiaoge Sun; Wei Zhong; Fengjv Zhao; Xiaomei Li; Sha Li; Hong Zhu; Zhanshu Ma; Ke Hu; et al. (BMC Cancer, 2024)
Abstract Background Endometrial cancer is a prevalent gynecologic malignancy found in postmenopausal women. However, in the last two decades, the incidence of early-stage has doubled in women under 40 years old. This study aimed to investigate the clinical and pathological characteristics and adjuvant therapeutic modalities of both young and not -young patients with early-stage endometrial cancer in China’s real world. Methods This retrospective study analyzed patients with early-stage endometrial cancer at 13 medical institutions in China from 1999 to 2015. The patients were divided into two groups: young (≤ 45 years old) and non-young (> 45 years old). Statistical comparisons were conducted between the two groups for clinical characteristics, pathological features, and survival. The study also identified factors that affect local recurrence-free survival (LRFS) using Cox proportional risk regression analysis. Propensity score matching (1:1) was used to compare the effects of local control between vaginal brachytherapy (VBT) alone and pelvic external beam radiotherapy (EBRT) ± VBT. Results The study involved 1,280 patients, 150 of whom were 45 years old or younger. The young group exhibited a significantly higher proportion of stage II, low-risk, lower uterine segment infiltration (LUSI), and cervical invasion compared to the non-young group. Additionally, the young patients had significantly larger maximum tumor diameters. The young group also had a significantly higher five-year overall survival (OS) and a five-year LRFS. Age is an independent risk factor for LRFS. There was no significant difference in LRFS between young patients with intermediate- to high-risk early-stage endometrial cancer who received EBRT ± VBT and those who received VBT alone. Conclusions In the present study, young patients had better characteristics than the non-young group, while they exhibited higher levels of aggressiveness in certain aspects. The LRFS and OS outcomes were better in young patients. Age is an independent risk factor for LRFS. Additionally, VBT alone may be a suitable option for patients under 45 years of age with intermediate- to high-risk early-stage endometrial cancer, as it reduces the risk of toxic reactions and future second cancers while maintaining similar local control as EBRT.